Existence of Solutions for a Schrödinger–Poisson System with Critical Nonlocal Term and General Nonlinearity - Jiafeng Zhang; Wei Guo; Changmu Chu; Hongmin Suo (Journal of Function Spaces)
We study the existence and multiplicity of nontrivial solutions for a Schrödinger–Poisson system involving critical nonlocal term and general nonlinearity. Based on the variational method and analysis technique, we obtain the existence of two nontrivial solutions for this system.